2020
DOI: 10.2176/nmc.oa.2019-0221
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate Effects of Vagus Nerve Stimulation in Intractable Epilepsy: An Intra-operative Electrocorticographic Analysis

Abstract: The purpose of this study was to investigate whether and how vagus nerve stimulation (VNS) reduces the epileptogenic activity in the bilateral cerebral cortex in patients with intractable epilepsy. We analyzed the electrocorticograms (ECoGs) of five patients who underwent callosotomy due to intractable epilepsy even after VNS implantation. We recorded ECoGs and analyzed power spectrum in both VNS OFF and ON phases. We counted the number of spikes and electrodes with epileptic spikes, distinguishing unilaterall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
3
10
0
Order By: Relevance
“…For example, if a particular desired outcome has been shown to correlate with an increase in theta band power, this target neuromodulatory state may be attainable by application of either 30 Hz iVNS or low amplitude taVNS. Though our sample size (n = 7) is comparable to recent studies 21,22 (though note that we sampled from a much larger set of electrodes, n = 1140), the high degree of variability we observed suggests that further work is needed to understand the multiple factors that contribute to different effects across modalities and individuals. It is also important to note that while in this study we elected to focus on acute changes in low-frequency spectral band power evoked by VNS, there are other complementary measures that were not examined here, such as functional connectivity 22 and vagal-evoked potentials 55 , across multiple time scales (i.e., acute vs. chronic effects 4 ).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…For example, if a particular desired outcome has been shown to correlate with an increase in theta band power, this target neuromodulatory state may be attainable by application of either 30 Hz iVNS or low amplitude taVNS. Though our sample size (n = 7) is comparable to recent studies 21,22 (though note that we sampled from a much larger set of electrodes, n = 1140), the high degree of variability we observed suggests that further work is needed to understand the multiple factors that contribute to different effects across modalities and individuals. It is also important to note that while in this study we elected to focus on acute changes in low-frequency spectral band power evoked by VNS, there are other complementary measures that were not examined here, such as functional connectivity 22 and vagal-evoked potentials 55 , across multiple time scales (i.e., acute vs. chronic effects 4 ).…”
Section: Discussionmentioning
confidence: 65%
“…We also observed that different cortical networks exhibited different responses to VNS (Fig. 2), which may explain why prior iEEG studies that only had access to a limited number of electrodes, produced conflicting results 20,21 . However, it is important to note that this caveat may apply to our findings as well.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Technological limitations, such as electrical current spread of ECS, no recording of EMG, sensitivity of BOLD signal in fMRI, different spatial resolution of two modalities, patients' awareness, and difference of extremity sites, may affect the results. 16 , 17 ) In addition, fMRI evaluates “voluntary movement,” whereas ECS induces movement by an active stimulation of the cortex. Therefore, we need to consider that these two modalities are observing a completely different aspect of motor control.…”
Section: Discussionmentioning
confidence: 99%
“…Recent fMRI findings showed distinct differences in effects between invasive VNS and transcutaneous VNS 18 . Additionally, invasive EEG studies on acute invasive VNS have found opposing effects of similar stimulation parameters on EEG spectral and broadband power 19 , 20 . A more recent finding suggests that while there may be variable results across cortical networks in the stereotactic EEG of different patients, in some individuals there are distinctly similar responses with certain stimulation paradigms 14 .…”
Section: Introductionmentioning
confidence: 99%